2006
DOI: 10.1093/nar/gkl582
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the apical stem–loop of the human hepatitis B virus encapsidation signal

Abstract: Hepatitis B virus (HBV) replication is initiated by HBV RT binding to the highly conserved encapsidation signal, epsilon, at the 5′ end of the RNA pregenome. Epsilon contains an apical stem–loop, whose residues are either totally conserved or show rare non-disruptive mutations. Here we present the structure of the apical stem–loop based on NOE, RDC and 1H chemical shift NMR data. The 1H chemical shifts proved to be crucial to define the loop conformation. The loop sequence 5′-CUGUGC-3′ folds into a UGU triloop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 47 publications
4
79
0
Order By: Relevance
“…Interhelical bend angles are also shown. The examples include the TBR, 84 domain II of HCV IRES (IIa), 119 SLD from the 5 0 UTR of enterovirus and rhinoviruses genomes (SLD), 120 a stem-loop at the 5 0 end of the HBV, 121 , stem-loop derived from helix-35 of E. coli 23S ribosomal RNA (Helix 35), 108 Tetrahymena thermophila SL-IV RNA in two variant constructs (SL-IV) 122 and (SL-IV-Fragment), 123 the CR4-CR5 domain in the vertebrate telomerase (hTR J6), 124 HIV-1 TAR RNA, 86 the frame-shift inducing element in HIV-1 (Frameshift), 125 RNase P P4, 126 HIV SL1m, 127 and the iron-responsive element (IRE). 87 NMR Studies of RNA Dynamics by RDCs 397 ble secondary structural rearrangement occurring at ls-ms timescales involving the internal loop and base-pairs in the upper stem.…”
Section: Figure 10mentioning
confidence: 99%
“…Interhelical bend angles are also shown. The examples include the TBR, 84 domain II of HCV IRES (IIa), 119 SLD from the 5 0 UTR of enterovirus and rhinoviruses genomes (SLD), 120 a stem-loop at the 5 0 end of the HBV, 121 , stem-loop derived from helix-35 of E. coli 23S ribosomal RNA (Helix 35), 108 Tetrahymena thermophila SL-IV RNA in two variant constructs (SL-IV) 122 and (SL-IV-Fragment), 123 the CR4-CR5 domain in the vertebrate telomerase (hTR J6), 124 HIV-1 TAR RNA, 86 the frame-shift inducing element in HIV-1 (Frameshift), 125 RNase P P4, 126 HIV SL1m, 127 and the iron-responsive element (IRE). 87 NMR Studies of RNA Dynamics by RDCs 397 ble secondary structural rearrangement occurring at ls-ms timescales involving the internal loop and base-pairs in the upper stem.…”
Section: Figure 10mentioning
confidence: 99%
“…Pseudotriloop (PTL) hairpins (Haasnoot et al 2002) or lonepair triloop hairpins (Lee et al 2003) are common, albeit rarely studied, structures in RNA (Addess et al 1997;Flodell et al 2002Flodell et al , 2006Kulinski et al 2003;Welting et al 2008). A PTL is proposed to form by creating a cross-loop base pair in an RNA hexaloop such that a triloop is created and the 3 ′ sixth loop base is bulged out (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…RNA loop structures with the potential to form PTLs are found in a variety of sequences, e.g., BMV (Haasnoot et al 2000(Haasnoot et al , 2002, domain IIId of the internal ribosomal entry site (IRES) of hepatitis C virus (Klinck et al 2000;Lukavsky et al 2000Lukavsky et al , 2003, RNAse MRP P3 domain (Welting et al 2008), HIV-1 TAR (Critchley et al 1993;Kulinski et al 2003), the apical loop of hepatitis B virus (HBV) ɛ domain (Flodell et al 2002(Flodell et al , 2006, and iron responsive element (IRE) (Sierzputowska et al 1995;Liang and Hall 1996;Hall and Williams 2004). The BMV, HBV, HCV, and IRE PTL structures have been established experimentally (Addess et al 1997;Lukavsky et al 2000;Flodell et al 2002Flodell et al , 2006Skov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the structural basis and sequence requirements for RT-e binding and priming are emerging, several questions remain and a full understanding of the molecular basis for the specific interactions between P and e awaits high-resolution structural and thermodynamic data. The importance of high-resolution structural data is underlined by the NMR studies of the human HBV e apical stem-loop, which showed that its conserved apical loop folds into a pseudotriloop, whereas secondary structure programs predicted a hexaloop (Flodell et al 2002(Flodell et al , 2006. A functional in-vitro RT-e replication system exists for Duck, but not for human HBV.…”
mentioning
confidence: 99%
“…Subsequently, a 4nt DNA primer is synthesized using the e-primer loop as template. The resulting complex translocates to a 3 0 -proximal e RNA element of the pgRNA, where full-length DNA synthesis is started using the 4-nt DNA as primer (Flodell et al 2006;Girard et al 2007;Petzold et al 2007). Although the structural basis and sequence requirements for RT-e binding and priming are emerging, several questions remain and a full understanding of the molecular basis for the specific interactions between P and e awaits high-resolution structural and thermodynamic data.…”
mentioning
confidence: 99%